Nikosthénès et l’Étrurie : échanges et appropriations transculturels ? - Lucille Garnery (Frontière·s)
The Athenian potter Nikosthenes is known to have included into his repertoire shapes and decorative elements of Etruscan origin inspired by the bucchero pottery. He also maintained special commercial bonds with certain cities, notably Cerveteri and Vulci in the second half of the 6th century BCE. Through a partial study of Nikosthenes’ work, we wish to examine the phenomenon of assimilation of bucchero shapes by an Athenian workshop, or rather of their adaptation with black-figure technique. These vases of Etruscan inspiration were produced almost exclusively for trade within their region of origin. How can this phenomenon be explained? To what degree was Nikosthenes involved in these innovations? How important was Etruscan demand? Were the customers only interested in the vases’ shapes and uses or did they also select images that suited them? Finally, we will analyse how the Etruscans integrated these Athenian imports into their own material and symbolic culture.